Numerical simulation of flow within a storage area of HDPE modular pavement - A. S. N., Amirah; F. Y., Boon; K. A., Nihla; Z. M., Salwa; A. W., Mahyun; N., Yaacof (IOP Publishing Ltd, 2021)
The development of stromwater management usually promote to provide the safe passage of stromwater. However physical modelling need expensive laboratory experiments. Due to that this numerical study is performed to study the flow within storage area of HDPE modular pavement. This paper studied and compared the infiltration rate of diagonal modular and conventional pavement (control), determined the velocity magnitude and pressure of modular pavement at various rainfall intensities. FLOW-3D was used to run a simulation on a porous media flow model using the Navier-Stokes equation. Real rainfall data of Malaysia was used as the model inputs to get better analysis of pavement design. The present findings showed that storage area modular pavement has lower fraction of fluid than control, which means that it has greater holding capacity and capable to capture all the rainfall volume from 5mm/h to 85mm/h. Besides, rainfall intensity has a strong influence on velocity magnitude and pressure. The HDPE diagonal modular pavement strong enough to sustain with an increasing of velocity magnitude and pressure during extreme rainfall. Therefore, HDPE modular pavement indicates a better water interception capacity than conventional pavement. FLOW-3D helps the critical analysis of pavement design process and useful as supplementary tool.